Micro-narratives : Tentation des petites réalités = Temptation of Small Realities. - Hegyi, Lóránd; Exhibition. Micro-narratives : Tentation des petites réalités = Temptation of Small Realities. Musée d'Art Moderne de Saint-Etienne Métropole. 2008-05-07. 2008-09-21; Aberbuch, Moti; Airyung, Kim; Andjelic Galic, Gordana; Arnautovic, Snezana; Badiola, Txomin; Bajic, Mrdjan; Bernard, Christian; Boubnova, Iara; Buergel, Roger, M.; Bush, Kate; et al. (Saint-Etienne : Musée d'Art Moderne de Saint-Etienne Métropole, 2008)
Alberola, Jean-Michel ; Andjelic Galic, Gordana ; Armleder, John ; Arnautovic, Snezana ; Badiola, Txomin ; Bajic, Mrdjan ; Barabash, Ruth ; Berruti, Valerio ; Binder, Erik ; Boggasch, Frauke ; Bosnic, Milan ; Bussmann, Maria ; Cabrita Reis, Pedro ; Calic, Marija ; Cano, Eugenio ; Cantoni, Davide ; Cernicky, Jiri ; Chust Peters, Daniel ; Civera, Victoria ; Coates, Marcus ; Cornet, May ; Djuric, Uros ; Dzafo, Nikola ; Eichhorn, Barbara ; Feriancová, Petra ; Friedl, Peter ; Friedmann, Gloria ; Gontarski, Steven ; Grassino, Paolo ; Gray, Kevin Francis ; Han, Soonja ; Hapaska, Siobhán ; Holcová, Veronika ; Horakova, Dominka ; Irazu, Pello ; Joatton, Marine ; Kim, Heeseok ; Kim, Hyunsoo ; Kim, Oan ; Kimsooja ; Kovacheva, Nina ; Lancaster, Laura ; Langlade, Fabrice ; Lehocká, Denisa ; Leikauf, Andreas ; Levini, Felice ; Löhr, Christiane ; Manon den Uyl, Tessa ; Mattii, Maria Carla ; McCaslin, Matthew ; Mezzaqui, Sabrina ; Millicevic, Milica ; Mizrachi, Motti ; Moizer, Zsuzsa ; Németh, Hajnal ; Noh, Sang-Kyoon ; Nolan, Isabel ; Palla, Ursula ; Paris, Marina ; Perez Simao, Marina ; Petrovic, Ivan ; Pétrovitch, Françoise ; Poljak, Renata ; Popovic, Zoran ; Prego, Sergio ; Prodanovic, Mileta ; Rajkovic, Hana ; Revesz, Laszlo Laszlo ; Rubiku, Anila ; Savini, Maurizio ; Seric, Nebojsa Soba ; Skart ; Stefanoff, Valentin ; Stojanovic, Marko ; Sung-Myung Chun ; Szépfalvi, Agnes ; Toguo, Barthélémy ; Vásquez de la Horra, Sandra ; Vedovamazzei ; Vidor, Vuk ; Vincourova, Katerina ; Weinberger, Lois & Franziska ; XYZ ; Yang, Haegue ; Yee, Sookyung ; Yoo, Hye-Sook ; Zuffi, Italo ; Zupanc, Ivan
biog., ind. tent., gr. tent. p. 209-224
boek
Keywords: Saint-Etienne